2022
DOI: 10.1038/s41598-022-20892-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between class of foundational medication for heart failure and prognosis in heart failure with reduced/mildly reduced ejection fraction

Abstract: We clarified the association between changes in the number of foundational medications for heart failure (FMHF) during hospitalization for worsening heart failure (HF) and post-discharge prognosis. We retrospectively analyzed a combined dataset from three large-scale registries of hospitalized patients with HF in Japan (NARA-HF, WET-HF, and REALITY-AHF) and patients diagnosed with HF with reduced or mildly reduced left ventricular ejection fraction (HFr/mrEF) before admission. Patients were stratified by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…Patients were frequently comorbid with hypertension, CKD, ischemic heart disease, and atrial fibrillation. These findings were in line with the recent reports from large-scale registries in Japan 9 , 20 . We found that one-third of patients initiated new HF medications, of which roughly three in four patients started these medications during hospitalization for HF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients were frequently comorbid with hypertension, CKD, ischemic heart disease, and atrial fibrillation. These findings were in line with the recent reports from large-scale registries in Japan 9 , 20 . We found that one-third of patients initiated new HF medications, of which roughly three in four patients started these medications during hospitalization for HF.…”
Section: Discussionsupporting
confidence: 92%
“…Despite its importance due to the high risk of HF readmission, comorbid burden, and the risk of HF decompensation events, there is currently limited information on changes in HF medications and the persistence of the treatment initiated after worsening HF events in Japan. Retrospective analyses of large-scale registries of patients hospitalized for HF reported the changes in HF medication patterns from admission to discharge; however, the longitudinal data on treatment continuations were lacking 9 , 20 . In a multinational study, patterns of titration and discontinuation of newly initiated GDMT after worsening HF events were reported; however, the study lacked data on other HF medications, such as diuretics and digoxin 21 .…”
Section: Introductionmentioning
confidence: 99%